ANALISIS KEMAMPUAN MENYUSUN PERANGKAT PEMBELAJARAN MAHASISWA PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU PADA MATA KULIAH PPL II T.A 2013/2014 - Mariani Natalina; Darmawati "; Dita Gusti Yarini (Biogenesis, 2016)
ABSTRACT The aim of this study was to determine the ability of the Student Profile Study Program FKIP Riau University Biology Education in Developing Learning Tool on Course PPL II 2013/2014. Research conducted at the University Campus Biology Education FKIP Riau in February 2015 to April 2015. This research is descriptive population in this research is the students of Biology Education FKIP Riau University. While the sample in this study are students who take courses Second Field Experience Program (PPL II) Academic Year 2013/2014 which amounted to 43 people. The research data derived from primary data obtained directly through the instrument in the form of sheets of assessment of learning tools and secondary data obtained from the document recapitulation of the value of the course PPL II Academic Year 2013/2014. Based on the research ability of students PPL II in preparing the study on subjects PPL II Academic Year 2013/2014 can be seen that the RPP showed excellent category criteria with the percentage of 95.17%, LKS demonstrate sufficient criteria categories by percentage of 62.33%, the Draft Evaluation criteria showed excellent category with the percentage of 87.78%, so that the students' ability to construct a learning tool in the course PPL II Academic Year 2013/2014 classified as excellent with the percentage of 81.7%. Key words:  profiles , capabilities , subjects PPL I